2001
DOI: 10.1002/ana.1051
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic enzyme expression in dopaminergic neurons in Parkinson's disease: An in situ hybridization study

Abstract: To clarify the role of neuronal complex 1 activity in idiopathic Parkinson's disease (IPD), expression of mitochondrial mRNA encoding the ND1 subunit of mitochondrial complex I was examined by semiquantitative in situ hybridization histochemistry in melanized neurons of human substantia nigra in IPD cases and control subjects. Expression of mRNA encoding the glycolytic enzyme, aldolase C, was also examined in substantia nigra and other neurons of the midbrain and brain stem. ND1 mRNA expression was strong in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…This view is supported by a recent study, performed using in situ hybridization histochemistry, which showed that mitochondrial ND1 mRNA expression is decreased in neuromelanin-containing substantia nigra neurons of patients with idiopathic PD (IPD), as compared to control subjects [Kingsbury et al, 2001]. As this decrease in mitochondrial Complex I activity in IPD may be involved in predisposing nigral neurons to degeneration, EGb 761 or bilobalide (by increasing the expression of ND1) could possibly be useful in preventing or delaying the progression of neurodegeneration in this disease.…”
Section: Commentsmentioning
confidence: 62%
See 1 more Smart Citation
“…This view is supported by a recent study, performed using in situ hybridization histochemistry, which showed that mitochondrial ND1 mRNA expression is decreased in neuromelanin-containing substantia nigra neurons of patients with idiopathic PD (IPD), as compared to control subjects [Kingsbury et al, 2001]. As this decrease in mitochondrial Complex I activity in IPD may be involved in predisposing nigral neurons to degeneration, EGb 761 or bilobalide (by increasing the expression of ND1) could possibly be useful in preventing or delaying the progression of neurodegeneration in this disease.…”
Section: Commentsmentioning
confidence: 62%
“…With specific regard to the study of Tendi et al [2002], their findings that EGb 761 and bilobalide increased the expression of the gene encoding ND1 could be relevant to developing therapy for PD, since oxidative stress and a selective defect in Complex I of OXPHOS (which is encoded by both mtDNA and nDNA) have been implicated in the progressive cell loss (mainly in dopaminergic neurons of the substantia nigra) that occurs in a subset of patients with this neurodegenerative disorder [see e.g., Przedborski et al, 1993;Swerdlow et al, 1996;Anglade et al, 1997;Kosel et al, 1998;Pettus et al, 2000;Chinopoulos and Adam-Vizi, 2001;Kingsbury et al, 2001]. This view is supported by a recent study, performed using in situ hybridization histochemistry, which showed that mitochondrial ND1 mRNA expression is decreased in neuromelanin-containing substantia nigra neurons of patients with idiopathic PD (IPD), as compared to control subjects [Kingsbury et al, 2001].…”
Section: Commentsmentioning
confidence: 96%
“…Indeed, we found that the first window of IPC could not protect mitochondria against the deficits in respiration through complexes I -IV [55]. Rates of respiration in presence of pyruvate + malate and succinate + glycerol -3 -phosphate decreased in both the ischemia and in IPC groups marginally.…”
mentioning
confidence: 76%
“…Lastly mitochondrial haplotypes in Caucasian patients (classified as haplotype J) markedly reduce the risk of developing PD [54]. The mRNA for the NDI subunit of mitochondrial complex I is reduced by 25% in the substantia nigra melanized neurons in PD [55].…”
Section: Mitochondrial Dysfunction In Pdmentioning
confidence: 99%
See 1 more Smart Citation